Intraoperative 3D imaging leads to substantial revision rate in management of tibial plateau fractures in 559 cases - Beisemann, Nils; Keil, Holger; Swartman, Benedict; Schnetzke, Marc; Franke, Jochen; Grützner, Paul Alfred; Vetter, Sven Y. (Journal of orthopaedic surgery and research, 2019)
Introduction: The aim of this study was to evaluate the intraoperative revision rate and reasons for revision following 3D imaging in the management of dislocated articular tibial plateau fractures based on a large patient sample. - Methods: This retrospective cohort study included all patients who underwent open reduction and internal fixation due type B or C tibial plateau fracture according to the AO/OTA classification between August 2001 and December 2017 using intraoperative cone beam CT (3D imaging) for the analysis of fracture reduction and implant placement. The findings of the 3D scan were categorized regarding the amount and type of revision. Furthermore, demographic data was examined. - Results: Five hundred and fifty-nine consecutive fractures were included in the study. Evaluation of the image data records revealed an intraoperative revision due to the usage of 3D imaging in 148 out of 559 cases (26.5%). The most common reasons for an intraoperative revision were insufficient fracture reduction (114 cases) and screw length (21 cases). - Conclusion: This study reveals indications for a limited analysis of fracture reduction and implant placement during the operative treatment of dislocated articular tibial plateau fractures using conventional fluoroscopy. In view of the high revision rate during open reduction and internal fixation of tibial plateau fractures due to 3D imaging the usage of intraoperative cone beam, CT may be considered. If this is not possible, a postoperative computed tomography may therefore be reasonable.
Gesehen am 02.03.2021